Variable urine Histoplasma antigen with volume status - Allyson Hughes; Joy Underwood; George E. Nelson; Richard W. Larue; Melissa L. Scalise (Greater Baltimore Medical Center, 2019)
A patient with progressive disseminated histoplasmosis was noted to have an increase in urine Histoplasma antigen level during monitoring of her disease. The patient revealed she had inadequately hydrated, and her urine volume was low and subjectively concentrated. Following hydration, urine antigen was retested and became undetectable.